2008
DOI: 10.1111/j.1540-8159.2008.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Prognosis after Primary Cardiac Resynchronization System Implantation Compared to “Upgrade” Procedures

Abstract: Upgrade patients showed similar baseline parameters and response to CRT as to primary implants. No difference in events or long-term prognosis could be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…CRT upgrade has been shown to be beneficial in HF patients resulting from long‐term RVP . Studies using tissue Doppler echocardiography have demonstrated improvement in LV synchronization following CRT upgrade . It has also been shown that the beneficial effects of CRT upgrade were similar to patients with de novo CRT for patients with HF and LBBB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRT upgrade has been shown to be beneficial in HF patients resulting from long‐term RVP . Studies using tissue Doppler echocardiography have demonstrated improvement in LV synchronization following CRT upgrade . It has also been shown that the beneficial effects of CRT upgrade were similar to patients with de novo CRT for patients with HF and LBBB .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CRT upgrade improved clinical outcomes and LV synchrony in patients with HF following long‐term RVP . Moreover, it has also been shown that the beneficial effects of CRT upgrade from long‐term RVP were similar to de novo CRT implantation for patients with HF and LBBB . The ACCF/AHA/HRS and ESC guidelines recommend CRT upgrade or de novo CRT implantation as class IIa indication for patients who have frequent dependence on ventricular pacing and LV ejection fraction (LVEF) ≤35%…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As healthier hearts can better compensate for wrong pacing sites and sequences, suboptimal pacing modalities exert more influence on natriuretic peptide levels in patients with left ventricular dysfunction. The largest difference in natriuretic peptide levels has been reported in patients with left ventricular dysfunction, when comparing cardiac resynchronization therapy and dual‐chamber pacing from the right ventricle or no pacing . Preservation of AV synchrony by atrial‐based or dual‐chamber pacing in general pacemaker population, versus ventricular‐only pacing, had the second strongest effect on peptide levels .…”
Section: Discussionmentioning
confidence: 98%
“…The patients showed subjective clinical improvement, fewer hospitalizations, and improved LV function. 30,45,[49][50][51][52][53][54][55][56][57][58][59] (1) Upgrading versus de novo cardiac resynchronization Several studies have shown that patients with RV pacing (and low LVEF) improved after upgrading to BiV pacing with a benefit that was comparable or even better than that observed in HF patients with native LV conduction delay who underwent de novo CRT implantation (followup 3-38 months). [60][61][62][63][64] The European CRT survey which compared 692 upgrades with 1675 de novo procedures at 141 centers in Europe, showed that there were no significant differences in clinical outcomes, mortality complication rates between upgrades and de novo procedures.…”
Section: Upgrade From Conventional Pacemaker or Icd To Crtmentioning
confidence: 97%